new technologies and technological capability-building at the enterprise level : some policy implications (UN New YorkUS, 1996)
Analyses the implications of new technologies in terms of the challenges posed and opportunities opened up for latecomer industrialization and the issues involved in technological capability-building especially at the enterprise level.
DC